Digital technologies in marketing: the case of university tunas - Gonçalves, Vitor (2024)
Digital technologies are currently present in all economic sectors of society and higher education as one of the basic sectors of contemporary society is no exception. Whether in the teaching-learning process, in other administrative and technical-pedagogical services, or in the student groups that make up the academic communities, technologies seem to play an important role in the development and operationalization of the various types of activities and processes that make up the different sectors of higher education institutions. It is in this context that the present research arises, which, in general, aims to identify the technologies adopted for the advertising and dissemination of the Tuna’s brand and image, but also to understand how the team responsible for this area uses these technologies in this area of digital marketing. To carry out the study, the case study methodology is adopted, whose focus will be on the “RaussTuna-Tuna Mista de Bragança”, Polytechnic Institute of Bragança (Portugal). The results suggest that this particular Tuna uses a set of digital technologies that help to operationalize its activity in the area of digital marketing. The results also show that each of the technologies has its own complexities, so the members who use them recognize having difficulties in using some of these tools. In this sense, it seems important to invest not only in the training of members in the area to acquire more digital skills, but also to invest in updating the various tools, platforms and software of the Tuna.